Dyskinesia Impairment Scale scores in Dutch pre-school children after neonatal therapeutic hypothermia. (September 2020) - Kuiper, M.J.; Meiners, L.C.; Chandler, E.S.; Brandsma, R.; Bos, A.F.; Horst, HJ ter; Sival, D.A.; Boyd, N.T.; Brouwer, O.F.; Elema, A.E.; Heineman, K.R.; et al.
Abstract: Background: Neonatal therapeutic hypothermia (TH) can ameliorate or prevent the development of dyskinetic cerebral palsy (CP) after hypoxic-ischemic encephalopathy (HIE). The Dyskinesia Impairment Scale (DIS) was recently launched to quantify dyskinetic (dystonic and choreatic) motor features in patients with CP. In TH treated children, who are at risk of developing dyskinetic CP, we aimed to determine DIS-scores at pre-school age. Method: In 21 Dutch pre-school children (3–6 years of age) who had received TH according to the Dutch-Flemish treatment protocol, we determined DIS-scores. We associated DIS-scores with 1. age-matched control values (Kuiper et al., 2018) [1], and 2. previously reported DIS-score range in dyskinetic CP (Monbaliu E et al., 2015). Results: The motor phenotype was determined as: normal (n = 18/21), mildly impaired (reduced coordination (n = 2/21)) and abnormal (dyskinetic CP; n = 1/21). In absence of CP (n = 20/21), DIS-scores were lower (more favorable) than in dyskinetic CP, without any overlapping group scores (mean difference: 71 points; p < .05 ). However, the obtained DIS-scores were still higher than previously reported in healthy age-matched controls (mean difference: 14 points; p < .05) . There was an association between DIS-scores and retrospective neonatal MRI (basal ganglia and thalamus injury on diffusion weighted imaging (DWI)) and (a)EEG parameters (p < .05 ). Conclusion: In the vast majority (95%) of Dutch TH-HIE treated pre-school children, the phenotypic motor outcome was favorable. However, DIS-scores were moderately increased compared with healthy age-matched controls. Future studies may elucidate the significance of moderately increased DIS-scores should to further extent. Highlights: Dutch pre-school children, that were treated by therapeutic hypothermia for hypoxic-ischemic encephalopathy, revealed: Favorable motor outcomes in the vast majority (95%) of children Clearly lower Dyskinesia Impairment Scale (DIS)-scores than reported in dyskinetic CP 1 Monbaliu E et al. Dev Med Child Neurol 2015; 58:138–44. Higher (less favorable) DIS-scores than in healthy age-matched controls a positive association between DIS-scores and the motor phenotype a positive association between DIS-scores and retrospective neonatal MRI/EEG parameters